(untitled) (Journal of actual problems of jurisprudence, 2020)
Within a market economy, the trends of agrarian, territorial and environmental legislation reforming are aimed at development of agricultural cooperation and ensuring phytosanitary security. For a long time eminent menaces from quarantine, extremely hazardous and undesirables directly affect the further development of agriculture, increasing biodiversity, as well as ensuring country’s food security. At the present moment, entitled issues are the premier sources that harm the economy of the State. This article deals with the legal support of phytosanitary security in the modern development of agricultural system of farming. In the time of active research writing, the author used methods of analysis and synthesis, generalization and classification. The primary objectives requiring shift solution are the scientific substantiation and the need of evaluation and risk management system applying restrictive quarantine measures in the field of state phytosanitary control (supervision). In this regard, ensuring the sustainable development of agricultural production, including organically pure agricultural products, is of particular importance. The author analyzes the current agricultural, land and environmental legislation of the Republic of Kazakhstan in the field of phytosanitary safety. Conclusions and suggestions on improving the activities of phytosanitary inspections are given. Key words: food security, phitosanitary security, phitosanitary control, protection and plant quarantine, agricultural industry, farming, agricultural cooperative society, rural sector, phitosanitary and quarantine demands.